One health genomic surveillance in the post-COVID-19 era: opportunities and challenges - Yee, Yu Choo; Zakaria, Zunita; Mat Isa, Nurulfiza; Ang, Geik Yong (Southeast Asia One Health University Network, 2024)
During the COVID-19 pandemic, genomic surveillance of SARS-CoV-2 by using next-generation sequencing (NGS) becomes an integral component for studying the viral evolution and identification of new variants so that mitigation strategies can be carried out efficiently. Globally, all the countries have invested handsomely on the setting up the sequencing facilities which enable rapid tracking and monitoring of COVID-19 with more than 16 million of genomic sequences of SARS-CoV-2 have been deposited into Global Initiative on Sharing All Influenza Data (GISAID). This is the for the first time a large amount of a viral genome has been sequenced and made available in such a short duration of time (~4 years). The importance of genomic surveillance is undebatable, and the availability of sequencing facilities has offered an opportunity to conduct genomic surveillance for other pathogens including bacteria and parasites at One Health interfaces (animal, human and environment). However, the lack of resources and knowledge in expanding the applications of NGS especially for One Health genomic surveillance may hamper the sustainability of genomic surveillance after the COVID-19 pandemic. In this study, we provide an overview of One Health genomic surveillance with an emphasis on utilizing existing sequencing facility and provides guidance on how to successfully adopt and implement One Health genomic surveillance. With proper planning, the adoption of One Health genomic surveillance for tracking various infectious diseases is realizable.